Carboxymethyl Celulose (CMC) from Snake Fruit (Salaca edulis Reinw) Kernel of “Pondoh Super”: Synthesis and Characterization - Sri Anggrahini; Djagal Wiseso Marsono; Agus Setiyoko; Amalia Wahyuningtyas (Indonesian Association of Food Technologists, 2017)
Snake fruits kernel has high cellulose content thus potential to be an alternative source of carboxylmethylcellulose (CMC) production. However there are several condition that have to be optimized to increase the CMC synthesis which are concentration of NaOH solution, NaMCA addition, and the reaction temperature based on the degree of substitution (DS). The aim of this study was to determine the optimum conditions of synthesis CMC from “Salak Pondoh Super” kernel. Some factors that likely influence the synthesis were concentration of NaOH solution , NaMCA addition, and the reaction temperature based on the degree of substitution (DS) as the responses. Synthesis of CMC was optimized using completely randomized design. The result then was characterized by several parameters including water content, viscosity, purity, Water Holding Capacity (WHC), Oil Holding Capacity (OHC), lightness, crystallinity, and FT-IR spectra. Optimization was achieved by the use of 15% NaOH solution, 5 gram NaMCA per 5 gram cellulose and reaction temperature of 55ºC. The characteristics of the optimized CMC were DS 0.825, purity 90.86%, water content of 7.16 (% wb), viscosity 3.86 cps, 142.72 yield (% db), WHC 2.37 (g/g), OHC 2.31 (g/g), lightness 78.48, and crystanillity 32.69%. The FT-IR spectra of snake fruit kernel CMC was similar with the CMC Standard.